STRATEGI MANAJEMEN PENDIDIKAN PADA UNIVERSITAS LAMBUNG MANGKURAT BANJARMASIN DALAM MENGHADAPI TANTANGAN GLOBALISASI - Riinawati Riinawati (Penerbit Lafadz Jaya, 2023)
This study aims to analyze the education management strategies implemented by Lambung Mangkurat University (ULM) in facing the challenges of globalization. The research method used is a qualitative approach with data analysis techniques through in-depth interviews with three informants, namely the Rector of ULM, Dean of the Faculty of Education, and Lecturer in Education Management. The interview results show that ULM has adopted several relevant strategies in responding to global changes. ULM realizes the importance of adaptation to global changes by implementing technology-based strategies and international collaboration. Overseas exchange and internship programs are an important part of ULM's efforts in empowering students with international learning experiences. The Faculty of Education at ULM continuously evaluates and updates the curriculum to ensure relevance and responsiveness to the needs of the job market influenced by globalization. In addition, ULM lecturers strive to improve teaching skills, integrate technology in learning, and facilitate students in developing creativity and adaptability to real-world situations. In conclusion, ULM has had relevant strategic measures in facing the challenges of globalization and strives to create graduates who are ready to compete at the international level.